Potensi Beberapa Senyawa Turunan dan Tumbuhan sebagai Antidepresan dengan metode skrining Komputasi : Literature Review - Vina Luthfiana Hasna; Erlangga Muhamad Prayuda; Rika Valensia; Aditya Putra Tama; Khamairah Azzahrawaani Hermawan; Lina Nurfadhila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Depression is a severe mental illness that is usually characterized by feelings of sadness or anxiety. Data reports that some 800,000 cases of suicide are the result of depression. Meanwhile, in Indonesia, individuals with depression are in the range of 6% of the total population. Another finding was by the Central Statistics Agency (2014) that at least 3.4 million youth aged 10-19 experienced mental disorders in 2013. This review article aims to provide readers with information regarding compounds that have the potential as antidepressants. The method used in this literature review is to search for reference sources in the form of scientific journals or scientific articles, both on a national and international scale, related to in silico testing of antidepressant compounds. Several compounds can be used as antidepressants. The most common receptors used to test antidepressant activity are 5-HT1A (5-hydroxytryptophan) and MAOA (Monoamine Oxidase A). Compounds that have potential as antidepressants include safrole from nutmeg, Curcuma longa active compounds, curcumin derivatives, Angelica archagelica extracts, Gingerol and shogaol in Zingiber officinale Constituents, Dehydrozingerone Compounds from Zingiber officinale extract, eicosanal and acetate phytol from Elatostem papillosum, L. -17, 1MeTIQ, and Aegeline in Aegle marmelos fruit extract,